Choice between economic reforms and political reforms: an empirical analysis for financial development / Azka Jamil Akhter and Saima Sarwar. - Akhter, Azka Jamil; Sarwar, Saima (Universiti Teknologi Mara Selangor, 2015)
The purpose of this study is to investigate the impact of economic and political reforms on the decisions related to Financial Sector development both in developed and developing nations. Panel of sixty nations divided almost equally in both sections for the time period 1990-2012 has been used. Using Discroll-Kraay Fixed Effect estimation technique, results revealed that in all cases either for whole panels or for separate developing and developed nations, process of economic reforms is playing most important role in the development of this sector among all other variables and this becomes more prominent in case of developed nations. While among political factors, role of Governance has been observed positive and strongly significant in its impact on the development of this sector for all cases. But Democracy showed positive effect only for developed nations not for developing nations which highlights this fact that consistency is the most required ingredient in case of economic development overall. Overall findings of the study helps in concluding that in case of developing countries, economic reforms are proving to be more fruitful and swift in their outcomes than political reforms.